Assessment of a cogeneration system for ceramic industry by using various exergy based economic approaches. (October 2022) - Caglayan, Hasan; Caliskan, Hakan
Abstract: This study presents various exergy based economic analyses of a gas turbine cogeneration system (COGEN) for a ceramic tile plant for five different reference environment temperatures. Specific Exergy Costing (SPECO) method, which uses fuel-product exergy approach and flow costs, and Exergy-Cost-Energy-Mass (EXCEM) method, which considers exergy loss and destruction with cost association, are used. It has been found that the irreversibilities due to chemical combustion reactions, occurring in the combustion chamber (CC) of the gas turbine unit, wall tile (WD) dryer and ground tile dryer (GD), have negative effects for the destructed exergy cost rate of themselves and overall system. In addition, depending on the destructed exergy cost ratio, the exergy based economic factor rates of these components are found to be lower than others. While the increase of the COGEN's and all of its components' destructed exergy cost rates are direct proportionally to the increase in the environment temperature, they are inversely proportional to the exergy based economic factor. As a result of the SPECO method, in the EXCEM method, the exergy cost parameters of the CC are much higher than the other components at all reference environment temperatures because of the high destructed exergy value of the CC. The system needs to be optimized in terms of eliminating the irreversibilities encountered intensively in the components such as CC, WD, GD. Consequently, these results show that the focus should be on the CC first, then on the WD and GD. Highlights: Specific Exergy Cost and Exergy-Cost-Energy-Mass analyses are performed to a cogeneration system for a ceramic tile plant and its components. Economic forecasting is considered for a cogeneration system designed for ceramic production plants. Effects of various environmental temperatures on exergy based analyses of a cogeneration system are investigated.